'Favourite places in school' for lower-set 'ability' pupils: school groupings practices and children's spatial orientations. Issue 4 (4th July 2017) - Brown, Ceri
ABSTRACT: This paper contributes to the recent turn within Children's Geographies concerned with understanding and illuminating educational inequalities. The focus is upon pupils assigned to lower 'ability' groupings, in a school under pressure to raise attainment. The objective of the paper is twofold, firstly to consider how school grouping practices affect children's sense of belonging in lessons, and secondly, to contextualise these findings against children's spatial orientations within the broader school environment. It is argued that a spatial focus may shed light upon the educational policy drivers that contribute to the exclusion of disadvantaged children. Neo-liberal imperatives of accountability and performance can be seen to shape hierarchies of belonging, where pupils' positioning in 'ability' groupings enables/limits the spatial agency that they can exert. Macro policy concerns are mapped onto micro school processes concerning the construction and governance of school spaces, using theoretical insights from Michel Foucault and R.D Sack.